Analisis Kualitas Semen Segar Kambing Persilangan Boer pada Umur Muda dan Dewasa - Sirat, M M P; Setio, S; Birawa, F R; Rabbani, R N; Arif, M D; Siswanto, S; Dakhlan, A (Politeknik Negeri Lampung, 2025)
This study aimed to analyze the effect of age on the fresh semen quality of Crossbred Boer Goats at young (8–12 months) and adult (13–16 months) ages. This case study was conducted in July 2024 at Kahfi Farm, located in Fajar Baru Village, Jati Agung District, South Lampung Regency, Lampung Province, involving three goats in each age group. The age determination of the goats was based on the replacement of their incisors. Fresh semen collection was performed using artificial vagina specifically designed for goats, in the morning, every four days, with a total of four repetitions. The observed variables included: (1) macroscopic semen quality, comprising color, odor, pH, consistency, and semen volume; and (2) microscopic semen quality, including mass movement and individual sperm motility. Data for each parameter were presented in tables as means and standard deviations (mean±SD) and analyzed quantitatively and descriptively by comparing the data for each variable between the young and adult age groups. The conclusion of this study was the fresh semen quality of Crossbred Boer goats in the adult age group (13–16 months) showed better values compared to the young age group (8–12 months), but the fresh semen from both age groups did not meet the requirements for frozen semen production to be used in artificial insemination